Constrained consensus over continuous‐time multi‐agent networks with state constraints, non‐convex input constraints and time delays. Issue 20 (11th February 2021) - Mo, Lipo; Yu, Yongguang
Abstract : This study considers the constrained consensus problem of continuous‐time multi‐agent networks with hypercube state constraints, non‐convex input constraints and non‐uniform delays. It is assumed that each agent can only perceive its own constraint sets, the communication graphs are switching over time and the joint communication graphs are strongly connected. By introducing the time‐varying gains and the constraint operators, a new distributed algorithm is proposed. Then, it is proved that the constraint consensus can be reached under the proposed algorithm by reduction, while the states and the inputs are constrained to stay at the corresponding constraint sets. Finally, simulation examples are given to examine the effectiveness of the proposed results.